Hypofractionated or Conventionally Fractionated Adjuvant Radiotherapy After Regional Lymph Node Dissection for High-Risk Stage III Melanoma. Issue 1 (January 2023) - Holtkamp, L.H.J.; Lo, S.; Drummond, M.; Thompson, J.F.; Nieweg, O.E.; Hong, A.M.
Abstract: Aims: Adjuvant radiotherapy can be beneficial after regional lymph node dissection for high-risk stage III melanoma, as it has been shown to reduce the risk of recurrence in the node field. However, the optimal fractionation schedule is unknown and both hypofractionated and conventionally fractionated adjuvant radiotherapy are used. The present study examined the oncological outcomes of these two approaches in patients treated in an era before effective systemic immunotherapy became available. Materials and methods: This retrospective cohort study involved 335 patients with stage III melanoma who received adjuvant radiotherapy after therapeutic regional lymph node dissection for metastatic melanoma between 1990 and 2011. Information on tumour characteristics, radiotherapy doses and fractionation schedules and patient outcomes was retrieved from the institution's database and patients' medical records. Results: Hypofractionated radiotherapy (median dose 33 Gy in six fractions over 3 weeks) was given to 95 patients (28%) and conventionally fractionated radiotherapy (median dose 48 Gy in 20 fractions over 4 weeks) to 240 patients (72%). Five-year lymph node field control rates were 86.0% (95% confidence interval 78.4–94.4%) for the hypofractionated group and 85.5% (95% confidence interval 80.5–90.7%) for the conventional fractionation group ( P = 0.87). There were no significant differences in recurrence-free survival (RFS) (41.7%, 95% confidence interval 32.5–53.5 versus 31.9%, 95% confidence interval 26.1–38.9; P = 0.18) or overall survival (41.2%, 95% confidence interval 32.1–52.8 versus 45.0%, 95% confidence interval 38.7–52.4; P = 0.77). On multivariate analysis, extranodal spread was associated with decreased RFS ( P = 0.04) and the number of resected lymph nodes containing metastatic melanoma was associated with decreased RFS ( P = 0.0006) and overall survival ( P = 0.01). Conclusion: Lymph node field control rates, RFS and overall survival were similar after hypofractionated and conventionally fractionated adjuvant radiotherapy. The presence of extranodal spread and an increasing number of positive lymph nodes were predictive of an unfavourable outcome. Highlights: Adjuvant radiotherapy for resected high-risk nodal melanoma is of value. Hypofractionated and conventionally fractionated adjuvant radiotherapy were compared. Node field recurrence, recurrence-free survival and overall survival were similar. Extranodal spread and number of positive lymph nodes predicted worse survival. Hypofractionated radiotherapy is easier for patients and reduces the costs to health systems.